KOMPETENSI KOMUNIKASI ANTAR BUDAYA ETNIK CINA BANGKA - Agustina Zubair (Indonesian Journal of Dialectics, 2013)
This study aims to describe the cultural identity of ethnic Chinese of Bangka related to self-perception of ethnic Chinese of Bangka and perception of ethnic Malay of Bangka about ethnic Chinese in a business relationship with the ethnic Malay of Bangka and intercultural communication competence of Bangka Chinese ethnic related to management of identity and self presentation in bussiness relationship with ethnic Malay of Bangka. Study of ethnic Chinese of Bangka intercultural communication competence in business relationship with the ethnic Malay of Bangka employs subjective approach and interpretive perspective and the phenomenological research tradition. The Phenomenological tradition focuses on individual perceptions and meaning in relation to the experience of intercultural communication competence which is experienced directly by the 25 ethnic Chinese as informants and 5 ethnic Malays as subjects of research. Communication activities that shaped cultural identity and intercultural communication competence which is experienced by informants is explored using in-depthinterviews and observations, producing the data in the form of statements and behaviors experienced by ethnic Chinese andethnic Malays of Bangka. The study found that (1) the cultural identity of ethnic Chinese of Bangka has self- perception that they are open and willing to Mingle, pay attention to courtesy and honesty, hardworking and tenacious of life-saving, descendants of the wise and civilized, Chenese farmer and the Chinese trader, different with the Malays in trading mindset, and prioritize longterm relationship. While the Bangka Malay's cultural identity is open, obedient to the teachings of Islam, would not justify the means such bribing, consumptive and ostentatious. Otherwise, in the view of Chinese descents of Bangka, the Bangka Malay is open and willing to mingle, Malay is easily seduced, love to be complimented and flattered, they are easy to feel complacent,consumptive, tend to like to show off, they (Malay) can't be trust in their word or dishonest. Malay "Dak Kawah Susah" or not willing to work hard, not thorough, not fussy, not a competitor, and Malays like friendly Chinese.In the opinion of Malays Bangka, the Ethnic Chinese justifies all means, use bribing, use of capital to set the Malay, rough, and want to mingle. (2) intercultural bussines communication competence of ethnic Chinese of Bangka formed when ethnic Chinese of Bangka manage the cultural identity differences and facework strategy through maintaining self-image with self-presentation tactics and improved selfimage by means of self identity adaptation. (3) model of intercultural business competency of Ethnic Chinese of Bangka that represents how the ethnic Chinese of Bangka ethnic Chinese to manage the relationship identity, cultural identity differences and facework strategy of ethnic Chinese Bangka when dealing bussines relationship with ethnic Malay by constructing selfimage maintenance by way of self-presentation tactics and improvements self-image by means of self-identity adaptation.